Vanishing Women : Magic, Film, and Feminism - Beckman, Karen Redrobe, 1971- (Book collections on Project MUSE., 2003)
Disappearing women as a persistent trope from nineteenth-century magic through contemporary theory, film, and psychoanalysis.